The synthesis of strigolactone is affected by endogenous ascorbic acid in transgenic rice for l-galactono-1, 4-lactone dehydrogenase suppressed or overexpressing - Yu, Le (Journal of plant physiology, 2020)
Copyright © 2020 Elsevier GmbH. All rights reserved.